Dampak Pekerja Migran Perempuan Terhadap Status Sosial Ekonomi Keluarga, Tingkat Pendidikan, dan Kesehatan Anak - Basrowi Basrowi (Kafa`ah: Journal of Gender Studies, 2019)
The increasingly limited employment resulting in increased unemployment, declining family income, deteriorating family economic status, abandoning children's education, and declining rates of child and child health have encouraged rural communities to become migrant workers. The purpose of this study was to empirically test the effect of remittance on family economic level, child's education level, and child health level. To answer the research problem used expost facto research model. The subjects of the study were migrant workers and former migrant workers from Lampung Province. The results of the research are new models and policy implications to strengthen the performance of BNP2TKI. The results conclude that remittances have positive impacts on improving family economic status, child education level, and child health.